Kawasaki disease: a comprehensive review - Osiejewska, Aleksandra; Wojtachnio, Dominika; Bartoszewicz, Jakub; Grądzik, Anna; Nowakowska, Izabela; Kudan, Małgorzata; Gorajek, Anna (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Kawasaki disease is an acute, self-limited vasculitis of medium arteries, and it affects children under 5 years old. It can lead to coronary artery aneurysms. Brief description of the state of knowledge: Pathogenesis of Kawasaki disease is unclear. The diagnosis is based on the clinical findings. The characteristic symptoms are polymorphous skin rashes, conjunctivitis, erythema, dryness, cracking and bleeding of the lips, erythema and swelling of palms and soles and cervical lymphadenopathy. Kawasaki disease is defined as a fever for 5 days accompanied by 4 or more of the diagnostic symptoms described above. The classic diagnosis is based on the exclusion of other diseases too. The diagnosis of incomplete Kawasaki disease is suggested if less than 4 main clinical features are found. It is the most common cause of acquired heart disease in children. Kawasaki disease can lead to coronary artery aneurysm, myocarditis and pericarditis so it is very important to treat this illness correctly. Basic treatment is a single infusion of intravenous immunoglobulin and high-dose aspirin. Recurrent Kawasaki disease (persistent fever after first line treatment with IVIG and aspirin) requires the same treatment as used for the first episode. Corticosteroids and immune-modulating therapies can be used as second and third line options. Quick recognition and early treatment result in a reduction of coronary artery abnormalities. Conclusion: This article reviews basic informations, history, epidemiology, pathophysiology, clinical presentation, diagnostic criteria, complications and treatment of Kawasaki disease.